« Agir en silence » : la scène de genre de Chardin et de Greuze - Prohászka, Erzsébet (Verbum – Analecta Neolatina, 2011)
Contrary to literary works, paintings do not speak. They are closely related to the notion of silence, although, for a long time, theorists of painting have held that pictures tell a story, that of a great event. The Royal Academy of Painting and Sculpture established a hierarchy of genres in painting, according to which historical painting was the most highly esteemed while genre painting was at the bottom of the hierarchy. Historical themes are naturally eventful; paintings often want to educate the public, they intend to say something. However, genre painting is fundamentally different. Most often, it represents an everyday life scene in which the protagonist is silently absorbed in their activity. In this paper, we will try to answer the following question: if genre painting does not intend to instruct the spectator, what does it express then? We will examine the paintings of Chardin, comparing them with those of Greuze, based on the writings of art critics of the 18th century.